The Potential Effects Of L-Carnitine Supplementation On Body Weight And Body Fat Percentage in Healthy and Overweight/Obese People: A Literature Review - Nadhifa Aulia Arnesya; Dominikus Raditya Atmaka (Universitas Airlangga, 2022)
Latar belakang: Obesitas telah menjadi masalah yang serius di seluruh dunia. Meskipun kampanye dan rekomendasi terkait modifikasi gaya hidup sudah ditegakkan, tren obesitas masih cukup meningkat. Selain modifikasi gaya hidup, suplementasi makanan tampaknya memiliki efek penurunan berat badan yang menjanjikan. Salah satu suplemen makanan paling populer adalah L-Carnitine. Tujuan: Untuk mengeksplorasi peran suplementasi L-Carnitine dalam memengaruhi berat badan, khususnya pada individu yang sehat dan obesitas. Ulasan: L-karnitin memiliki peran penting dalam metabolisme asam lemak rantai panjang di mitokondria. Konsumsi 500 mg sampai 1 g suplemen L-Carnitine dalam 12 minggu terbukti menurunkan berat badan di antara peserta dengan status gizi gemuk dan obesitas. Suplementasi L-Carnitine juga memiliki efek yang signifikan pada penurunan massa lemak pada subjek dengan status gizi normal dan obesitas. Kesimpulan: Suplementasi L-Carnitine menunjukkan hasil pada penurunan berat badan dan pengurangan massa lemak terutama pada individu dengan status gizi gemuk dan obesitas yang melakukan latihan fisik dan menjalani pembatasan kalori. ABSTRACT Background: Obesity has become a serious problem worldwide. Despite established lifestyle modification campaign and recommendation, obesity trend remains increasing. In addition to lifestyle modification, dietary supplementation seemingly has a promising weight-reduction effect. One of the most popular dietary supplement is L-Carnitine. Objectives: This study aimed to comprehend potential roles of L-Carnitine supplementation on weight loss, specifically in healthy, overweight, and obese individuals. Discussion: L-Carnitine plays a key role in long-chain fatty acid metabolism in mitochondria. The consumption of 500 mg to 1 g of L-Carnitine supplementation within 12 weeks was shown to decrease weight among overweight and obese participants. Moreover, L-Carnitine supplementation has a significant and direct effect on fat mass reduction in subjects with normal BMI and obesity. Conclusions: L-Carnitine supplementation may show results in weight loss and fat mass reduction especially among obese and overweight individuals who performed physical exercise and underwent calorie restricted diet.